What is wrong with inequality? - Satz, D; White, S (Oxford University Press, 2024)
This article lays out the reasons we have for objecting to certain differences between what individuals have and in how they relate to one another. Our aim is to show that there is a plurality of reasons to be concerned with such differences and not simply with the absolute amount that each individual has considered independently. Furthermore, we argue against a limited focus on income inequality. Other forms of inequality can also matter.